Two androecious mutations reveal the crucial role of ethylene receptors in the initiation of female flower development in Cucurbita pepo. (27th July 2020) - García, Alicia; Aguado, Encarnación; Garrido, Dolores; Martínez, Cecilia; Jamilena, Manuel
Summary: Ethylene is the key regulator of sex determination in monoecious species of the family Cucurbitaceae. This hormone determines which individual floral meristems develop as female or male flowers and the female flowering transition. The sex determination genes discovered so far code for ethylene biosynthesis enzymes, but little is known about the importance of ethylene signaling components. In this paper we characterize two novel ethylene‐insensitive mutations ( etr1a‐1 and etr1b ) which block the female flowering transition of Cucurbita pepo ; this makes plants produce male flowers indefinitely (androecy). Two missense mutations in the ethylene‐binding domain of the ethylene receptors CpETR1A or CpETR1B were identified as the causal mutations of these phenotypes by using whole‐genome resequencing. The distinctive phenotypes of single and double mutants for four etr mutations have demonstrated that the final level of ethylene insensitivity depends upon the strength and dosage of mutant alleles for at least three cooperating ETR genes, and that the level of ethylene insensitivity determines the final sex phenotype of the plant. The sex phenotype ranges from monoecy in ethylene‐sensitive wild‐type plants to androecy in the strongest ethylene‐insensitive ones, via andromonoecy in partially ethylene‐insensitive plants. The induction of female flowering transition was found to be associated with upregulation of CpACS11, CpACO2 and CpACS27, three ethylene biosynthesis genes required for female flower development. A model is proposed herein, integrating both ethylene biosynthesis and receptor genes into the genetic network which regulates sex determination in C. pepo . Significance Statement: Ethylene receptors not only regulate the fate of the floral meristem towards a female, hermaphrodite or male flower but are also involved in the female flowering transition. In fact, two mutations in ethylene receptors completely block this transition and result in plants that produce only male flowers (androecy). The interaction between different ethylene receptors, as well as other ethylene biosynthesis genes, has been studied to propose a model for sex determination in Cucurbita pepo .